2001
DOI: 10.1053/bbmt.2001.v7.pm11787531
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of highly purified CD34+Thy-1+ hematopoietic stem cells in patients with recurrent indolent non-Hodgkin's lymphoma

Abstract: CD34+Thy-1+ HSCs can be collected successfully from most lymphoma patients mobilized with G-CSF alone. The engraftment and disease outcomes in the patients in this small pilot study using these cells do not appear to be different from the outcomes of similar patients cited in the literature. However, the short- and long-term risks of infection were a concern in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…+ cells provided longterm engraftment while being purged of unwanted cancer or T cells (Michallet et al 2000;Negrin et al 2000;Vose et al 2001). All of these data combined support the idea that HSCs are contained in the Lin…”
Section: Cd90mentioning
confidence: 99%
“…+ cells provided longterm engraftment while being purged of unwanted cancer or T cells (Michallet et al 2000;Negrin et al 2000;Vose et al 2001). All of these data combined support the idea that HSCs are contained in the Lin…”
Section: Cd90mentioning
confidence: 99%
“…Additional studies have demonstrated that human HSC also express CD90 (3)(4)(5). Perhaps the best demonstration of HSC function comes from human clinical trials of autologous mobilized peripheral blood in clinical transplantation, where long-term engraftment was provided by transplantation of purified CD34ϩCD90ϩ cells (6)(7)(8). In multiple reports (12)(13)(14), a common phenotype for AML LSC has been identified and found to be negative for expression of lineage markers (Lin-), positive for expression of CD34, and negative for expression of CD38 (9 -11).…”
mentioning
confidence: 99%
“…CD34 enrichment yields a population of cells enriched for HSC and blood progenitor cells, but still contains many other cell types. However, limited trials in which highly FACSpurified CD34 pos CD90 pos H S C s w e r e u s e d a s a s o u r c e o f r e c o n s t i t u t i n g c e l l s h a v e demonstrated that rapid reconstitution of the blood system can reliably be obtained using only HSCs (Negrin et al, 2000;Vose et al, 2001). …”
Section: Haematopoietic Stem Cell Markersmentioning
confidence: 99%